Alternative Energetics DC Microgrid With Hydrogen Energy Storage System - Zaļeskis Genadijs; Steiks Ingars (Electrical, Control and Communication Engineering)
This paper is related to an alternative energetics microgrid with a wind generator and a hydrogen energy storage system. The main aim of this research is the development of solutions for effective use of the wind generators in alternative energetics devices, at the same time providing uninterrupted power supply of the critical loads. In this research, it was accepted that the alternative energetics microgrid operates in an autonomous mode and the connection to the conventional power grid is not used. In the case when wind speed is low, the necessary power is provided by the energy storage system, which includes a fuel cell and a tank with stored hydrogen. The theoretical analysis of the storage system operation is made. The possible usage time of the stored hydrogen depends on the available amount of hydrogen and the consumption of the hydrogen by the fuel cell. The consumption, in turn, depends on used fuel cell power. The experimental results suggest that if the wind generator can provide only a part of the needed power, the abiding power can be provided by the fuel cell. In this case, a load filter is necessary to decrease the fuel cell current pulsations.